2014
DOI: 10.1002/ange.201405647
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde‐Assisted Ruthenium(II)‐Catalyzed CH Oxygenations

Abstract: Versatile ruthenium(II) complexes allow for site‐selective CH oxygenations with weakly‐coordinating aldehydes. The challenging CH functionalizations proceed with high chemoselectivity by rate‐determining CH metalation. The new method features an ample substrate scope, which sets the stage for the step‐economical preparation of various bioactive heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In 2013, Jiao and co‐workers described a novel PdCl 2 and NHPI co‐catalyzed direct C( sp 2 )–H hydroxylation of 2‐phenylpyridines under neutral conditions with only 2‐(pyridin‐2‐yl)phenol being obtained . In 2014, Ackermann reported the ruthenium‐catalyzed C–H oxygenation with the assistance of weakly coordinating aldehydes . In 2015, Chakraborti developed a Pd‐catalyzed aryl C( sp 2 )–H activation with bioactive and sterically hindered heterocyclic moieties and other acyclic functionalities (azo, amide, anilide, carbamate and urea) as versatile directing groups with Na 2 S 2 O 8 as the oxidant .…”
Section: Methodsmentioning
confidence: 99%
“…In 2013, Jiao and co‐workers described a novel PdCl 2 and NHPI co‐catalyzed direct C( sp 2 )–H hydroxylation of 2‐phenylpyridines under neutral conditions with only 2‐(pyridin‐2‐yl)phenol being obtained . In 2014, Ackermann reported the ruthenium‐catalyzed C–H oxygenation with the assistance of weakly coordinating aldehydes . In 2015, Chakraborti developed a Pd‐catalyzed aryl C( sp 2 )–H activation with bioactive and sterically hindered heterocyclic moieties and other acyclic functionalities (azo, amide, anilide, carbamate and urea) as versatile directing groups with Na 2 S 2 O 8 as the oxidant .…”
Section: Methodsmentioning
confidence: 99%
“…Transition metal catalyzed CÀ H activation reaction of aromatic aldehyde is very limited and challenging because of their excessive tendency to undergo oxidation under the metal catalyzed oxidative reaction salicyldehyde (Scheme 45). [59] The intramolecular and intermolecular kinetic isotope effect (KIE) experiments established the coordination of aldehyde carbonyl with ruthenium catalyst for activation of ortho CÀ H bond.…”
Section: Phi(otfa) 2 Mediated Hydroxylationmentioning
confidence: 99%
“…to obtain best yield of salicyldehyde (Scheme 45). [59] The intramolecular and intermolecular kinetic isotope effect (KIE) experiments established the coordination of aldehyde carbonyl with ruthenium catalyst for activation of ortho C−H bond.…”
Section: Tfa− From Tfa and Phi(otfa)2 As Hydroxylating Agentmentioning
confidence: 99%
“…17 With the development of transition metal-catalyzed C─hydrogen (H) activation, direct C─H hydroxylation was regarded as one of the efficient avenues for the introduction of the desired functional group on the selected targets. [18][19][20][21][22][23][24][25][26][27][28][29] Therefore, it was considered as a novel strategy to obtain functionalized phenols based on the hydroxylation of inert C─H bonds. In 2010, Pan and co-workers reported that 2-(phenylthio)phenols could be smoothly synthesized from phenols and aromatic halides through C─H functionalization.…”
Section: Introductionmentioning
confidence: 99%